Alcohol Consumption and Cancer Risk: A Meta-Analysis and Systematic Review in Germany - Soleimani, Yaser; Sadeghi, Hamid; Ahmadi, Amir Mohammad; Emadi, Kosar; Elyasi, Arian; AhangarKani, Ali; Shariati Far, Nima; Daraei, Mahdi; Sabeti, Setareh; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Alcohol consumption is a prevalent behavior in Germany, deeply rooted in cultural traditions and societal norms. The relationship between alcohol consumption and cancer risk has been extensively studied globally, with evidence suggesting a positive association. However, the nuances of this association within the German population remain to be fully elucidated, considering the diverse patterns of alcohol consumption and regional variations in cancer incidence. Methods: This protocol outlines the methodology for a systematic review and meta-analysis aimed at examining the association between alcohol consumption and cancer risk in Germany. A comprehensive search strategy will be employed to identify relevant studies published until 2024. Inclusion criteria will encompass observational studies reporting on alcohol consumption levels and cancer incidence or mortality outcomes among adults in Germany. Data extraction, quality assessment, and statistical analyses will be conducted following established guidelines, including subgroup analyses based on alcohol type, consumption level, and cancer type. Results: The anticipated results will include a synthesis of the literature on alcohol consumption and cancer risk in Germany. The protocol expects to identify a substantial number of studies meeting the inclusion criteria, providing a robust dataset for meta-analysis. The meta-analysis will explore the association between alcohol consumption and overall cancer risk, as well as conduct subgroup analyses to investigate differential associations with specific cancer types based on alcohol type and consumption level. Conclusion: This protocol outlines a systematic approach to examining the association between alcohol consumption and cancer risk in Germany. The anticipated results will contribute to a better understanding of this relationship within the German population, informing evidence-based public health interventions and policy initiatives aimed at reducing the burden of alcohol-related cancers.